2012
DOI: 10.1007/s00265-012-1363-y
|View full text |Cite
|
Sign up to set email alerts
|

Sperm storage reflects within- and extra-pair mating opportunities in a cooperatively breeding bird

Abstract: In passerine birds, storage and maturation of sperm takes place in the cloacal protuberance (CP), an external swelling of the reproductive organ. The considerable variation in CP size among species is presumed to be a consequence of varying levels of sperm-competition, but whether individual variation in CP size within a species also reflects sperm competition is not well established. Here, we study temporal variation in male CP size in relation to within-pair and extra-pair mating opportunities and cuckoldry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Then, how is the synchronization in breeding date achieved among individuals involving in an EP mating event? According to the temporal change of male cloacal protuberance (the site of sperm maturation and storage) in the purple‐crowned fairy‐wren Malurus coronatus , Kingma et al () showed that male fertility is determined primarily by the breeding cycle of his social partner, typically around the fertile period of the female. Based on this finding, Kingma et al () thought that incestuously mated female in this species might adjust egg‐laying time to match the peak fertility of their preferred (genetically dissimilar) EP males to avoid fitness loss from inbreeding depression.…”
Section: Discussionmentioning
confidence: 99%
“…Then, how is the synchronization in breeding date achieved among individuals involving in an EP mating event? According to the temporal change of male cloacal protuberance (the site of sperm maturation and storage) in the purple‐crowned fairy‐wren Malurus coronatus , Kingma et al () showed that male fertility is determined primarily by the breeding cycle of his social partner, typically around the fertile period of the female. Based on this finding, Kingma et al () thought that incestuously mated female in this species might adjust egg‐laying time to match the peak fertility of their preferred (genetically dissimilar) EP males to avoid fitness loss from inbreeding depression.…”
Section: Discussionmentioning
confidence: 99%
“…Body mass (to nearest 0.1 g) and tarsus (to nearest 0.1 mm) were measured. Cloacal protuberance (CP, site of sperm storage) was measured in males ( n = 132 captures of 59 individuals), and volume was calculated following Kingma, Hall, and Peters ().…”
Section: Methodsmentioning
confidence: 99%
“…The influence of climate variation was analysed on (a) timing of initiation of breeding attempts (date of laying of the first egg of a clutch), (b) body mass (corrected for structural size), (c) male sperm storage (cloacal protuberance size, a proxy for readiness to breed; Kingma et al, ) and (d) food availability (monthly arthropod abundance). For all four biological responses, we set out to determine (a) the phenological critical time window: the time period of a climate variable (rainfall or temperature) that explains most of the variation of these biological responses, and (b) the nature of this relationship (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Territories are aligned linearly along the rivers, and boundaries and groups are stable year-round and across years (Hall and Peters 2008;Kingma et al 2011). Breeding can take place year-round but peaks in the monsoonal wet season (December to March) (Hall and Peters 2009;Kingma et al 2012). A strength of our study system is that only the dominant breeding pair engages in duets Peters 2008, 2009), providing a reliable cue to assign breeder (dominant) or subordinate status to each individual independent of submissive or aggressive interactions.…”
Section: Study Site and Speciesmentioning
confidence: 99%